Antiallodynic and anti-hyperalgesia effects of Tiliacora triandra against cisplatin-induced peripheral neuropathy. Issue 1 (1st January 2021) - Liu, Chunhong; Ma, Mingming; Wen, Chaoling; Uz Zaman, Raihan; Olatunji, Opeyemi Joshua
Abstract : Cisplatin (CISP) is one of the most commonly used drug for treating various cancers and solid tumours, however, its usage has been heavy restricted due to its deleterious side effects including peripheral neuropathy. Therefore, this study describes the anti-hyperalgesia and anti-allodynia effects of Tiliacora triandra (TTE) in CISP induced peripheral neuropathy. Peripheral neuropathy was established in rats by intraperitoneal injection of 2.5 mg/kg of CISP once a week for 4 weeks and the rats were concurrently treated with TTE (250 and 500 mg/kg, po) daily for 5 weeks. After the treatment, thermal hyperalgesia, motor coordination (rotarod test), mechanical allodynia, acetic acid writhing and formalin tests were evaluated. The rats were sacrificed and blood samples were collected for estimation of haematological parameters. TTE significantly restored motor coordination deficits induced by CISP and TTE-treated rats showed marked improvement in thermal/chemical hyperalgesia and mechanical allodynia. Additionally, treatment with TTE also increased haematological parameters including haemoglobin, platelet count, WBC and RBC compared to CISP-treated group. These findings demonstrated that TTE effectively ameliorated CISP induced peripheral neuropathic pain in a cisplatin paradigm.